MRT ads to feel it and donate for KGCC's elephant / Siti Zubaidah Abd Rahman - Abd Rahman, Siti Zubaidah (Faculty of Art and Design, 2020)
The gentle elephant needs attention. An elephant is animal that have a very soft heart.